KEMAMPUAN MENULIS TEKS DESKRIPSI PADA SISWA KELAS VII SMP NEGERI 3 TELUK KERAMAT - Lismi Lismi; Abdussamad Abdussamad; Ahmad Rabi’ul Muzammil (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study generally discussed the class VII of SMPN 3 Teluk Keramat students’ skills in writing the descriptive text and specifically discussed their skills from the aspects of title, structures, and the use of language. This study aims to describe the skills in writing a descriptive text on the class VII students of SMPN 3 Teluk Keramat in academic year 2019/2020. his research implemented a descriptive study with the form of quantitative and qualitative. The sample was taken using a random sampling technique. The data was collected using indirect communication with the data collection tool in the form of a written test. The analysis revealed that the learners’ writing skills, according to the aspect of title was categorized as excellent by 88.57%. In the aspect of the structure divided into three, namely identification and description with excellent category by respectively 87.85% and 89.28%, and closing structure with the satisfactory category by 61,42%. In the aspect of language use, however, was categorized as unsatisfactory by 45%.  Keywords: Descriptive Text, Language use, Text Structure, Tittle, Writing Skill